VOLODIMIR SOSYURA LIFE IN BONDAGE AND OBSTRUCTION - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Volodimir Sosyura, a prominent Ukrainian poet with tragic fate, entered the consciousness of generations as a symbol of invincibility in the tragic years of slavery and persecution. He never deviated from the Ukrainian idea and even threatened with death bequeathed his contemporaries and descendants like Ukraine. All poet's life was between the steel mills that tried to crush him and killing mentally and physically. Banned and removed unwanted Soviet system his works and books in 1924, 1927, 1929, 1931, 1932, 1951 years. Confiscated even manuscripts and collections. His mentally and physically crucified, always keeping in the long, deep depression and nervous exhaustion, and creative life in a state of social, national and family oppression.The creative and physically hiding from arrest, poet didnt masked his views, as evidenced not betrayed his love for his native land, which he carried until his balancing between life and death.